ANALYSIS OF THE INFLUENCE OF ORGANIZATIONAL CULTURE AND COMMUNICATION ON EMPLOYEE JOB SATISFACTION AT THE HEAD OFFICE OF THE DIRECTORATE GENERAL OF CUSTOMS AND EXCISE - Parinding, Triyanta Gala; Rangkuti, Zulkifli; Listiorini, Dewi (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2025)
The population is 85 employees of the Head Office of the Directorate General of Customs and Excise by calculating the sample size using the Slovin formula technique. There is an influence of organizational culture on work effectiveness, it is proven that the t value for the organizational culture variable (X1) is 3,491 while the t table value for N = 85 is 1,988. So 3,491 > 1,988, then H0 is rejected and Ha is accepted, it can be stated that organizational culture (X1) has a significant effect on employee job satisfaction (Y). There is an influence of Communication on Work Effectiveness, it is proven that the tcount value for the Communication variable (X2) is 7,222, while the ttable value for N = 85 is 1,988. So 7,222 > 1,988, then H0 is rejected and Ha is accepted, it can be concluded that partially the Communication variable (X2) has an effect on employee job satisfaction (Y). There is an influence of organizational culture and communication together on work effectiveness, as evidenced by the ANOVA test, the Fcount value is 75.695, while the Ftable ( 0.05) for N = 85 is 2.71. So Fcount > from Ftable ( 0.05) or 75,695 > 2.71 with a significant level of 0.000 because 0.000 < 0.05 then it can be said that organizational culture (X1) and communication (X2) together or simultaneously have a positive effect on satisfaction. employee work (Y). Based on the calculations in the table above, the influence was tested for the three variables, and based on the Model Summary table, the Adjusted R Square (R2) value was 0.649. This shows that 64.9% of organizational culture (X1) and communication (X2) together influence employee job satisfaction (Y), while the remaining 35.1% is influenced by other factors not examined in this research.